Co-occurring factors associated with suicidal ideation among individuals with parole involvement: A classification and regression tree analysis - Leah MCCOY; Javier F. BOYAS; Sung Seek MOON; Michael A. ROBINSON; Onick LEWIS; Amy E. COX (Journal of Health and Social Sciences)
Introduction: Formerly incarcerated individuals on parole burden a higher risk of suicidality compared to the general public. This study explored specific physical health, mental health, and substance use predictors contributing to suicidal ideation among individuals with parole involvement. Methods: Pooled data from the National Survey on Drug Use and Health were analyzed through a CART analysis to uncover co-occurring interactions associated with suicidal ideation among a national sample of individuals with parole involvement (N=1,725). Results: Total acute depression scores, both lower and higher, had a significant impact on suicidal ideation. Milder forms of depression were significant when they intersected with unaddressed mental health needs, ADL limitations, and pain reliever misuse. More severe depression symptoms compounded mental health challenges, particularly when they coincided with ADL limitations, a poorer perception of health, and the unique experiences of individuals at both ends of the adult spectrum, particularly those aged 18-20 and individuals aged 35 years or older. Results suggest that depression symptoms were the most influential variable associated with suicidal ideation. Conclusion: Although considerable efforts have been made in research and practice to shed light on these issues, there has been a noticeable lack of focus on the provision of community resources and mental health treatment during and post incarceration. It is imperative to recognize that most people in the criminal justice system eventually reintegrate into our communities. Thus, it becomes vital to bridge the gap by offering treatment and resources during incarceration.